2020
DOI: 10.48550/arxiv.2008.10749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breaking the Communities: Characterizing community changing users using text mining and graph machine learning on Twitter

Abstract: The formation of majorities in public discussions often depends on individuals who shift their opinion over time. The detection and characterization of these type of individuals is therefore extremely important for political analysis of social networks. In this paper, we study changes in individual's affiliations on Twitter using natural language processing techniques and graph machine learning algorithms. In particular, we collected 9 million Twitter messages from 1.5 million users and constructed the retweet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A retweet graph was defined in terms of G = (N, E), where users were nodes N and retweets between them were edges E (Albanese et al, 2020). Since a user could retweet multiple times other user's tweets, the edges were weighted.…”
Section: Community Pooling:mentioning
confidence: 99%
See 2 more Smart Citations
“…A retweet graph was defined in terms of G = (N, E), where users were nodes N and retweets between them were edges E (Albanese et al, 2020). Since a user could retweet multiple times other user's tweets, the edges were weighted.…”
Section: Community Pooling:mentioning
confidence: 99%
“…Considering that LDA allows multiple topics in one single document, having longer documents with denser co-occurence matrix has been shown to be beneficial (Alvarez-Melis & Saveski, 2016). Also, other works had shown that tweets belonging to users of one community in the retweet network were mostly of one or two topics (Albanese et al, 2020).…”
Section: Community Pooling:mentioning
confidence: 99%
See 1 more Smart Citation